Prevalence and determinants associated with T. pallidum infection in adults from poor urban communities, Brazilian Amazon - Lucas Bittencourt Dantas; Bruna Tais Rocha Damasceno; Janaina de Freitas Vale; Wanne Thaynara Vaz Gurjao; Lorena Saavedra Siqueira; Sávio Felipe Dias Santos; Marília de Fátima Vieira de Oliveira; Cintia Yolette Urbano Pauxis Aben-Athar; Eliã Pinheiro Botelho; Glenda Roberta Oliveira Naiff Ferreira (Elsevier, 2024)
Background: In Brazil, despite the increase in coverage and access to rapid testing for syphilis in primary health care, no reduction in cases of syphilis and congenital syphilis was observed. Poor and low-educated populations are disproportionately affected by infection caused by T. pallidum. This study aims to estimate the prevalence of syphilis and associated factors among people aged 18 to 49 years old in the city of Belém, brazilian amazon. Methods: Observational, cross-sectional study carried out in a sanitary administrative district of a capital of the Brazilian Amazon, Belém, state of Pará, Brazil. Data collection was conducted from August 2021 to February 2022. The participantes consisted of residents of the Montese, Guamá and Condor neighborhoods. People aged 18 to 49 years were included. This variable was treated as dichotomous (reagent and non-reagent). The selected response event was 'reagent result'. The independent variables were the social factors and access to health services. To identify associated factors with the presence of markers of the bacteria studied, multiple logistic rules were performed. Results: 178 people participated in the study; the median age was 35.0 years. The prevalence of IgG and/or IgM antibodies against T. pallidum was 7 % (13). In the final regression model, it was observed that participants who had sexual intercourse after using alcohol and drugs and those who did not know about the prevention of sexually transmitted infections were five times more likely to have tested positive for T. pallidum. Conclusions: Aspects of individual vulnerability and access to health services must be managed to reduce the exposure of poor urban populations to T. pallidum.